AN ANALYSIS OF THE EFFECTS OF COMPENSATION AND WORK ENGAGEMENT ON EMPLOYEE PERFORMANCE IN THE PRODUCTION DEPARTMENT AT PT PANELINDO FURNITECH MULTIGUNA, SERANG REGENCY - Siti Muhaeni Indriyanti; Khaeruman Khaeruman; Aria Cendana Kusuma (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to examine the influence of K compensation and work engagement on employee performance, both partially and simultaneously, within the production department of PT Panelindo Furnitech Multiguna in Serang Regency, which has experienced a downward trend in production target achievement since March 2026, allegedly due to sub-optimal management of these two factors. This study employs a survey method using a quantitative approach. The study population and sample comprised all 77 employees in the production department, using a saturation sampling technique. Data were collected through observation, literature review, and a Likert-scale questionnaire, and subsequently analyzed using SPSS version 25 via classical assumption tests, multiple linear regression, the coefficient of determination test, the t-test, and the F-test. The results indicate that Compensation (X1 ) has a positive and significant effect on Employee Performance (Y) (tcalculated  8.842 > ttable 1.66543; sig. < 0.001), whilst Job Commitment (X2 ) showed a negative relationship with tcalculated  -2.531 and sig. 0.013. Taken together, Compensation and Job Commitment have a significant effect on Employee Performance (Fcalculated  40.623 > Ftable  3.120; sig. < 0.001), with a coefficient of determination (R²) of 0.523 or 52.3%. It is concluded that compensation is the most dominant factor in improving Employee Performance in this study.